Validity of a jump mat for assessing countermovement jump performance in elite rugby players - Dobbin, N.; Hunwicks, R.; Highton, J.; Twist, C. (International Journal of Sports Medicine, 2017)
This study determined the validity of the Just Jump System® (JJS) for measuring flight time, jump height and peak power output (PPO) in elite rugby league players. 37 elite rugby league players performed 6 countermovement jumps (CMJ; 3 with and 3 without arms) on a jump mat and force platform. A sub-sample (n=28) was used to cross-validate the equations for flight time, jump height and PPO. The JJS systematically overestimated flight time and jump height compared to the force platform (P<0.05), but demonstrated strong associations for flight time (with R2=0.938; without R2=0.972) and jump height (with R2=0.945; without R2=0.987). Our equations revealed no systematic difference between corrected and force platform scores and an improved the agreement for flight time (Ratio limits of agreement: with 1.00 vs. 1.36; without 1.00 vs. 1.16) and jump height (with 1.01 vs. 1.34; without 1.01 vs. 1.15), meaning that our equations can be used to correct JJS scores for elite rugby players. While our equation improved the estimation of PPO (with 1.02; without 1.01) compared to existing equations (Harman: 1.20; Sayers: 1.04), this only accounted for 64 and 69% of PPO.